Inovasi Snack Bar Sirih Cina (Peperomia Pellucida) Sebagai Alternatif Pemenuhan Nutrisi Atlit Renang - Ita Fatkhur Romadhoni; Muhammad Kharis Fajar; Satwika Arya Pratama (Lembaga Pengembangan Kinerja Dosen, 2025)
The main objective of the research was to produce a snack bar that is not only delicious but also rich in nutrients, especially those obtained from Chinese betel leaves. The research process involved formulation, sensory testing, and nutritional analysis to ensure that this product meets the nutritional standards required by swimming athletes. The results showed that the Chinese betel leaf-based snack bar innovation was able to improve the nutritional adequacy of swimming athletes 40% better than consuming energy supplements with increased swimming duration in the range of 15 minutes / training session. These findings have implications for improving athletes' nutritional intake, supporting optimal recovery, and ultimately, improving their performance in training and competition.